Hyperosmolar Hyperglycemic Crisis After Burn Injury in a Patient With Advanced Amyotrophic Lateral Sclerosis: A Case Report. Issue 4 (October 2022) - Lin, Meng-Wei; Chang, Yu-Tzu; Hsueh, Yuan-Yu
Abstract: Metabolic disturbance in patients of amyotrophic lateral sclerosis is a rare presentation that might be related to disease progression and outcomes. Hypermetabolic status after major burn injury remains a critical issue in the modern medical care. Here, we present a rare case of a patient sporadic amyotrophic lateral sclerosis who suffered from minor burn injury (8% total body surface area), developing critical hyperosmolar hyperglycemic state during early hospitalization. Newly diagnosed diabetes is established and found related to the underlying disease of this patient. The accumulative metabolic alteration among vulnerable patients of amyotrophic lateral sclerosis and burn injury is noteworthy. Judicious monitoring of fluid and metabolic status helps to prevent the occurrence of acute hyperosmolar hyperglycemic state.